Autosub Long Range 1500: A continuous 2000 km field trial - Alexander B. Phillips; Robert Templeton; Daniel Roper; Richard Morrison; Miles Pebody; Philip M. Bagley; Rachel Marlow; Ed Chaney; James Burris; Alberto Consensi; Davide Fenucci; Francesco Fanelli; et al. (Ocean Engineering, 2023)

Mentoring in the USDA Forest Service: A Survey of Aquatic Professionals - Lee Cerveny; Nabin Baral; Brooke Penaluna; Brett Roper; Daniel Shively; Shelly Witt (Journal of Forestry, 2023)
Mentoring is suggested as an important strategy to promote workplace inclusivity and is shown to be positively associated with high employee morale, yet mentee needs and experiences may not be universal. To evaluate mentoring impacts from the perspective of USDA Forest Service employees, we conducted an online survey of 251 aquatic professionals, including managers and scientists. 70% of respondents had mentors, and mentorship status did not vary across demographic characteristics. Previous mentoring relationships were most frequently identified as “informal” rather than “formal”; female employees were more likely to desire formal mentoring. Mentored respondents found their work more challenging, fulfilling, and valuable than unmentored respondents. Mentees looked for mentors who could provide constructive feedback, speak candidly, use active listening skills, and who cared about their careers. Overall, respondents were satisfied with their mentors’ skills. Despite strong demand for mentoring, access to mentors among aquatic professionals appears low across all categories.

Broad‐scale eDNA sampling for describing aquatic species distributions in running waters: Pacific lamprey Entosphenus tridentatus in the upper Snake River, USA - Michael K. Young; Daniel J. Isaak; David Nagel; Dona L. Horan; Kellie J. Carim; Thomas W. Franklin; Victoria A. Zeller; Brett Roper; Michael K. Schwartz (Journal of Fish Biology, 2022)
One of the most fundamental yet challenging tasks for aquatic ecologists is to precisely delineate the range of species, particularly those that are broadly distributed, require specialized sampling methods, and may be simultaneously declining and increasing in different portions of their range. An exemplar is the Pacific lamprey Entosphenus tridentatus , a jawless anadromous fish of conservation concern that is actively managed in many coastal basins in western North America. To efficiently determine its distribution across the accessible 56,168 km of the upper Snake River basin in the north‐western United States, we first delimited potential habitat by using predictions from a species distribution model based on conventionally collected historical data and from the distribution of a potential surrogate, Chinook salmon Oncorhynchus tshawytscha , which yielded a potential habitat network of 10,615 km. Within this area, we conducted a two‐stage environmental DNA survey involving 394 new samples and 187 archived samples collected by professional biologists and citizen scientists using a single, standardized method from 2015 to 2021. We estimated that Pacific lamprey occupied 1875 km of lotic habitat in this basin, of which 1444 km may have been influenced by recent translocation efforts. Pacific lamprey DNA was consistently present throughout most river main stems, although detections became weaker or less frequent in the largest and warmest downstream channels and near their headwater extent. Pacific lamprey were detected in nearly all stocked tributaries, but there was no evidence of indigenous populations in such habitats. There was evidence of post‐stocking movement because detections were 1.8–36.0 km upstream from release sites. By crafting a model‐driven spatial sampling template and executing an eDNA‐based sampling campaign led by professionals and volunteers, supplemented by previously collected samples, we established a benchmark for understanding the current range of Pacific lamprey across a large portion of its range in the interior Columbia River basin. This approach could be tailored to refine range estimates for other wide‐ranging aquatic species of conservation concern.

3D Printing of Metformin HCl PVA Tablets by Fused Deposition Modeling: Drug Loading, Tablet Design, and Dissolution Studies - Mariam Ibrahim; Morgan Barnes; Robert McMillin; Daniel W. Cook; Sarah Smith; Mathew Halquist; Dayanjan Wijesinghe; Thomas D. Roper (AAPS PharmSciTech, 2019)

Global patterns of interaction specialization in bird–flower networks - Thais B. Zanata; Bo Dalsgaard; Fernando C. Passos; Peter A. Cotton; James J. Roper; Pietro K. Maruyama; Erich Fischer; Matthias Schleuning; Ana M. Martín González; Jeferson Vizentin‐Bugoni; Donald C. Franklin; Stefan Abrahamczyk; et al. (Journal of Biogeography, 2017)
Aim Among the world's three major nectar‐feeding bird taxa, hummingbirds are the most phenotypically specialized for nectarivory, followed by sunbirds, while the honeyeaters are the least phenotypically specialized taxa. We tested whether this phenotypic specialization gradient is also found in the interaction patterns with their floral resources. Location Americas, Africa, Asia and Oceania/Australia. Methods We compiled interaction networks between birds and floral resources for 79 hummingbird, nine sunbird and 33 honeyeater communities. Interaction specialization was quantified through connectance ( C ), complementary specialization ( H 2 ′), binary ( Q B ) and weighted modularity ( Q ), with both observed and null‐model corrected values. We compared interaction specialization among the three types of bird–flower communities, both independently and while controlling for potential confounding variables, such as plant species richness, asymmetry, latitude, insularity, topography, sampling methods and intensity. Results Hummingbird–flower networks were more specialized than honeyeater–flower networks. Specifically, hummingbird–flower networks had a lower proportion of realized interactions (lower C ), decreased niche overlap (greater H 2 ′) and greater modularity (greater Q B ). However, we found no significant differences between hummingbird– and sunbird–flower networks, nor between sunbird– and honeyeater–flower networks. Main conclusions As expected, hummingbirds and their floral resources have greater interaction specialization than honeyeaters, possibly because of greater phenotypic specialization and greater floral resource richness in the New World. Interaction specialization in sunbird–flower communities was similar to both hummingbird–flower and honeyeater–flower communities. This may either be due to the relatively small number of sunbird–flower networks available, or because sunbird–flower communities share features of both hummingbird–flower communities (specialized floral shapes) and honeyeater–flower communities (fewer floral resources). These results suggest a link between interaction specialization and both phenotypic specialization and floral resource richness within bird–flower communities at a global scale.

White-rumped swallows prospect while they are actively nesting - Uschi Wischhoff; Fernando Marques-Santos; Daniel R. Ardia; James J. Roper (Journal of Ethology, 2015)